Potentials of synchrotron radiation induced X-ray standing waves and X-ray reflectivity measurements in material analysis - Krämer, Markus (Technische Universität Dortmund, 2007)
In this work the potentials of two X-ray methods, X-ray reflectivity (XRR) and X-ray standing waves (XSW) at grazing incidence (including X-ray fluorescence), using synchrotron radiation are experimentally evaluated. First, the theory of X-ray scattering in general, X-ray reflectivity, X-ray fluorescence and X-ray standing waves is discussed. Then, a focus is set onto calculation of X-ray standing waves at grazing angle of incidence. The experimental procedures for the above mentioned methods are outlined, and a combination of XRR and XSW is presented. Further, a computer program developed in this work to calculate X-ray standing waves intensity fields and permit evaluation of XSW scans is introduced. Finally, a wide variety of different layered and layer-like samples is presented that were characterized by a combination of XSW and XRR. The samples ranged from semiconductor samples (germanium layers on silicon substrates and implantations of As, Co and Zn ions in Si wafers), to bio-organic samples (cytochrome and nitrobenzene films, phospholipid bilayers as a model for biological membranes, metal-organic layers such as gold or silver clusters on polymer films), a multilayer laser mirror and ion distributions in a buffer solution. It is shown that the combination of XRR and XSW is especially powerful in comparison to other methods for samples that show little optical contrast between the layers (e.g. biological material) or are otherwise difficult to characterize by established methods. Further, the developed computer program permits evaluation of complicated structures not accessible by standard software.
Keywords: X-ray standing waves; XSW; X-ray reflectivity; XRR; X-ray fluorescence; XRF; Layers; nm; Semiconductor; Biofilms; Synchrotron; Material analysis; 660